Permeable asphalt steel slag concrete and preparation method thereof
By using filling enhancement technology of steel slag fine aggregate, matrix asphalt and limestone ore powder in asphalt mixture, combined with basalt coarse aggregate and SBS modified asphalt, high-performance permeable asphalt steel slag concrete is prepared, which solves the problem of poor stability of steel slag water, improves water damage resistance and durability, and reduces costs.
Patent Information
- Application Number
- CN202310198840.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-03
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-03-03
AI Technical Summary
Steel slag has poor water stability in asphalt mixture, which limits its efficient use in highway engineering.
High-performance permeable asphalt steel slag concrete is prepared by mixing the fine steel slag aggregate, matrix asphalt and limestone ore powder to form a fill reinforcement aggregate and mix it with basalt coarse aggregate, SBS modified asphalt and asphalt reinforcement.
It significantly improves the water damage resistance and durability of asphalt steel slag concrete, reduces the overall construction cost, and reduces the impact of steel slag expansion when exposed to water.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of traffic engineering building materials and relates to a high-performance permeable asphalt steel slag concrete and a preparation method thereof. Background Art
[0002] Steel slag contains free calcium oxide (f-CaO) and free magnesium oxide (f-MgO), which expand in volume when exposed to water, greatly limiting its efficient use. Exploring ways to improve the efficiency and added value of steel slag has become a key common problem in many infrastructure construction industries.
[0003] Since steel slag is currently only partially used in the cement and building materials industries, seeking high value-added utilization methods in other industries, conducting in-depth joint research with other industries, and jointly reducing carbon emissions are the most likely and effective ways to resolve the steel slag problem.
[0004] As infrastructure construction continues to increase, the coverage of highway projects is also expanding, the consumption of highway materials is increasing, and it is also facing difficulties such as increased crushed stone costs and reduced crushed stone quality. Considering the physical and chemical properties of steel slag, while ensuring the quality of engineering construction, research on using steel slag to replace part or all of the earth and stone materials can not only reduce the cost of the project, but also reduce the resource consumption of the steel industry.
[0005] Research and engineering applications have shown that when unpretreated coarse-grained steel slag (particle size > 4.75mm) is added to the asphalt mixture, there are significant problems with the water stability of the mixture; when fine-grained steel slag materials (particle size ≤ 4.75mm) or steel slag powder is added, due to the relatively good stability of the steel slag itself (small particle size: small pores, short pore depth, and no connectivity), the impact on the water stability of the mixture is limited (can be used for road base or surface layers of highways below grade three), and the problem can be solved by pretreatment methods such as resin sealing (increasing processes and costs).
[0006] Before 2020, the research on dense and impermeable asphalt steel slag concrete in China focused on two aspects: 1) Regardless of the type of asphalt, starting from the perspective of partially replacing fine aggregate (10-60%, particle size ≤4.75mm), only using the particle size shape of steel slag with smaller particle size close to cube and better angularity to increase the contact area between aggregate particles inside the concrete, that is, to improve the mechanical strength and anti-friction deformation ability of the skeleton structure formed by the mutual intercalation of aggregates (stones), thereby improving the resistance to permanent deformation, high temperature and water stability of asphalt steel slag concrete, avoiding the problem of poor water stability of steel slag with larger particle size (particle size ≥4.75mm) when encountering water. 2) Regardless of the large surface tension and poor wettability of modified asphalt, attempts were made to use the porous properties of steel slag to absorb more asphalt, but due to insufficient filling, free water with good wettability and strong penetration (dynamic water pressure caused by high-speed vehicle operation) was given space to form a water film interlayer, reducing the anti-peeling performance of asphalt on the aggregate surface. Therefore, for the base asphalt with low viscosity and good wettability, the modification effect is still good (the low temperature, anti-aging, durability and other properties are still poor, and it cannot be used in secondary and above roads); as for the currently widely used and relatively expensive SBS, high viscosity and other modified asphalts, due to their own high viscosity and poor wettability, the modification effect is unstable and not obvious, resulting in the current application of asphalt steel slag concrete in highways of all grades and urban roads.
[0007] Permeable asphalt concrete, also known as porous asphalt concrete, is one of the main pavement materials for the current "sponge city" construction. Rainwater runoff will often soak asphalt concrete and even penetrate into the asphalt-aggregate interface. These will pose challenges to the large-scale replacement rate and efficient utilization of steel slag (particle size ≥ 2.36mm) with poor stability (to water) to replace aggregates in asphalt mixtures.
[0008] At present, there is an urgent need to increase the replacement ratio of steel slag, especially the particle size between 2.36mm-9.5mm, and widely use various types of modified asphalt with high viscosity and poor wettability to significantly improve the high / low temperature, water damage resistance, aging resistance and durability of asphalt steel slag concrete, so that it can be widely used in secondary and above highways and urban roads. Summary of the invention
[0009] The purpose of the present invention is to provide a high-performance permeable asphalt steel slag concrete and a preparation method thereof, so as to solve the problem of poor water stability of steel slag in steel slag-based permeable asphalt concrete.
[0010] The purpose of the present invention can be achieved by the following technical solutions:
[0011] A method for preparing permeable asphalt steel slag concrete comprises the following steps:
[0012] S1: Mix steel slag fine aggregate, matrix asphalt and limestone powder evenly to obtain filling and reinforcing aggregate;
[0013] S2: Mix the filling reinforced aggregate with basalt coarse aggregate, SBS modified asphalt and asphalt enhancer, mix them evenly, and obtain permeable asphalt steel slag concrete.
[0014] Furthermore, the mass ratio of the basalt coarse aggregate, steel slag fine aggregate, limestone powder, matrix asphalt, SBS modified asphalt, and asphalt enhancer is (60-80):(15-20):(3.5-5.5):(1.3-1.5):(4.2-5.0):(0.5-0.6).
[0015] Furthermore, in step S1, the mixing time is 30 to 60 seconds.
[0016] Furthermore, in step S2, the mixing time is 60 to 120 seconds.
[0017] Furthermore, the steel slag fine aggregate includes the following components and contents by weight:
[0018] 5-15 parts of steel slag fine aggregate with average particle size of 4.75-2.36 mm;
[0019] 5-10 parts of steel slag fine aggregate with an average particle size of 2.36-1.18 mm;
[0020] 3-8 parts of steel slag fine aggregate with average particle size of 1.18-0.075 mm.
[0021] Furthermore, the limestone powder is an ultrafine powder with a specific surface area of 5000-8000cm 2 / g, particle size distribution D90 is 55-65μm, and apparent relative density is 2.85-3.05g / cm 3 .
[0022] Furthermore, the basalt coarse aggregate includes the following components and contents by weight:
[0023] 0-5 parts of basalt coarse aggregate with an average particle size of 16.0-13.2 mm;
[0024] 50-70 parts of basalt coarse aggregate with an average particle size of 13.2-9.5 mm;
[0025] 10-20 parts of basalt coarse aggregate with average particle size of 9.5-4.75 mm.
[0026] Furthermore, the asphalt enhancer contains 0.16-0.2 wt% of tetrasodium ethylenediaminetetraacetate.
[0027] Furthermore, in the SBS modified asphalt, the mass ratio of the linear modifier SBS to the base asphalt is 4.5:100.
[0028] A permeable asphalt steel slag concrete is prepared by the method as described above.
[0029] The present invention utilizes 1) the high fluidity, high wettability and high pull-out resistance of the relatively hard and brittle matrix asphalt, which fills and seals the micron-sized holes densely distributed on the surface of the steel slag fine aggregate and the mineral powder, thereby minimizing the space and penetration for free water infiltration, that is, significantly reducing the influence of the water swelling characteristics of the steel slag, and forming a rivet structure with strong water-resistant stripping performance on the surface of the steel slag and the mineral powder; and 2) the good similarity and compatibility between the matrix asphalt and the SBS modified asphalt and the asphalt enhancer, further improving the fatigue resistance and water damage resistance of the rivet structure during service, thereby forming a high-performance permeable steel slag asphalt concrete.
[0030] Compared with the prior art, the present invention has the following characteristics:
[0031] 1) The present invention is based on a relatively brittle and relatively cheap matrix asphalt, which does not require additional pretreatment steps, and minimizes the space and penetration of free water into the micron-level holes on the surface of steel slag and mineral powder, that is, significantly reduces the influence of the water expansion characteristics of steel slag, and forms a rivet structure with strong water-resistant peeling performance on the surface of steel slag and mineral powder (a matrix asphalt of a suitable proportion); further, based on the thermal Brownian motion and density flow characteristics of liquid molecules, asphalt modifier SBS and asphalt enhancer are used in the mixing process to continuously improve the durability and water damage resistance of the matrix asphalt rivet structure, and finally the water damage resistance index of the permeable steel slag asphalt concrete is increased from about 83% to more than 95% (Marshall specimen freeze-thaw splitting strength ratio), the durability is increased by 20-30% (dynamic stability of rutting plate specimen), and the comprehensive cost is reduced by 10-15%;
[0032] 2) The present invention uses a matrix asphalt that is cheap, has good bonding properties with modified asphalt, and has high pull-out resistance with aggregates, but is relatively brittle, highly fluid, and highly wettable, to fill and seal the micron-sized holes densely distributed on the surface of steel slag fine aggregate (fine aggregate replacement rate is 100%) and mineral powder, rather than resin materials to seal the holes. This technology can minimize the space and penetration of free water infiltration (dynamic water pressure caused by high-speed vehicle operation), prevent the formation of water film interlayers at the asphalt-aggregate interface (inside and deep in the holes), and improve the anti-peeling performance of asphalt at the aggregate interface, that is, it can significantly reduce the influence of the steel slag swelling characteristics when it encounters water, and form a rivet structure with strong water-resistant peeling performance on the surface of steel slag and mineral powder (a matrix asphalt of a suitable proportion), and at the same time, utilize the good similarity and compatibility between the matrix asphalt and SBS modified asphalt and asphalt enhancer to further improve the fatigue resistance and water damage resistance of the rivet structure. DETAILED DESCRIPTION
[0033] The present invention is described in detail below with reference to specific embodiments.
[0034] A permeable asphalt steel slag concrete comprises basalt coarse aggregate, steel slag fine aggregate, limestone powder, matrix asphalt, SBS modified asphalt, asphalt enhancer, and the mass ratios are (60-80):(15-20):(3.5-5.5):(1.3-1.5):(4.2-5.0):(0.5-0.6);
[0035] The preparation method comprises the following steps:
[0036] S1: Mix the steel slag fine aggregate, matrix asphalt and limestone powder for 30 to 60 seconds to obtain filling and reinforcing aggregate; this step utilizes the high fluidity, high wettability and high pull-out resistance of the matrix asphalt with relatively large hardness and brittleness with aggregate to fill and seal the micron-level holes densely distributed on the surface of the steel slag fine aggregate and the mineral powder, thereby minimizing the space and penetration of free water infiltration, that is, significantly reducing the influence of the water expansion characteristics of the steel slag, and forming a rivet structure with strong water-resistant peeling performance on the surface of the steel slag and the mineral powder;
[0037] The matrix asphalt in the present invention is to fill and seal the micron-sized holes densely distributed on the surface of steel slag fine aggregate and mineral powder, and form a rivet structure with double rivet heads, so the amount used is only 18-25% of the total mass of asphalt required for high-performance permeable asphalt steel slag concrete;
[0038] Among them, steel slag fine aggregate includes the following components and contents by weight:
[0039] 5-15 parts of steel slag fine aggregate with average particle size of 4.75-2.36 mm;
[0040] 5-10 parts of steel slag fine aggregate with an average particle size of 2.36-1.18 mm;
[0041] 3-8 parts of steel slag fine aggregate with average particle size of 1.18-0.075 mm;
[0042] S2: Mix the filling reinforced aggregate with basalt coarse aggregate, SBS modified asphalt and asphalt enhancer, and mix for 60 to 120 seconds to obtain permeable asphalt steel slag concrete; this step utilizes the good similarity and compatibility between the matrix asphalt and the SBS modified asphalt and asphalt enhancer to further improve the fatigue resistance and water damage resistance of the above-mentioned rivet structure during service;
[0043] The basalt coarse aggregate includes the following components and contents by weight:
[0044] 0-5 parts of basalt coarse aggregate with an average particle size of 16.0-13.2 mm;
[0045] 50-70 parts of basalt coarse aggregate with an average particle size of 13.2-9.5 mm;
[0046] 10-20 parts of basalt coarse aggregate with average particle size of 9.5-4.75 mm.
[0047] In SBS modified asphalt, the mass ratio of linear modifier SBS to base asphalt is 4.5:100;
[0048] The asphalt enhancer contains 0.16-0.2wt% of tetrasodium ethylenediaminetetraacetate, which has a chelating and solidifying effect on metal ions on the surface of steel slag, and has the ability to complex magnesium-rich and calcium-rich hard water that invades the steel slag / basalt aggregate-asphalt interface, thereby significantly improving the durability and water damage resistance of permeable asphalt steel slag concrete.
[0049] The following embodiments are implemented based on the above technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following embodiments.
[0050] In the following examples, basalt coarse aggregate was purchased from Suzhou Sanchuang Pavement Engineering Co., Ltd. with two types of basalt aggregates of 5-10 mm and 10-15 mm; steel slag fine aggregate was purchased from Hebei Tonghua Highway Materials Co., Ltd. with two types of steel slag fine aggregates of 0-5 and 3-5 mm; limestone powder was purchased from Suzhou Sanchuang Pavement Engineering Co., Ltd., which is wear-resistant and ultra-fine limestone powder with a specific surface area of 5000-8000 cm 2 / g, particle size distribution D90 is 55-65μm, and apparent relative density is 2.85-3.05g / cm 3 ; The base asphalt was purchased from Suzhou Sanchuang Pavement Engineering Co., Ltd., South Korea's Ssangyong asphalt; SBS modified asphalt was purchased from Suzhou Sanchuang Pavement Engineering Co., Ltd., SBS-4.5 asphalt, in which the mass ratio of linear modifier SBS to base asphalt was 4.5:100; asphalt enhancer was purchased from Tongluda (Shanghai) Transportation Technology Co., Ltd., a high-elastic and crack-resistant asphalt enhancer, and contained 0.18wt% of tetrasodium ethylenediaminetetraacetic acid.
[0051] Embodiment 1:
[0052] A high-performance permeable asphalt steel slag concrete, comprising the following components and their contents in parts by weight:
[0053]
[0054]
[0055] The preparation method comprises the following steps:
[0056] S1: Mix steel slag fine aggregate, matrix asphalt and limestone powder for 50 seconds to obtain filling reinforcement aggregate;
[0057] S2: Mix the filling reinforcement aggregate with basalt coarse aggregate, SBS modified asphalt and asphalt enhancer, and mix for 90s to obtain permeable asphalt steel slag concrete.
[0058] This embodiment combines the preparation and testing methods of permeable asphalt concrete specimens in the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011):
[0059] 1) The water damage resistance index of high-performance permeable steel slag asphalt concrete (porosity of 20%) is 94.5% (freeze-thaw splitting strength ratio of Marshall specimen), and the durability index is 4300 times / mm (dynamic stability of rutting plate specimen). The comprehensive cost of 4cm thick high-performance permeable steel slag asphalt concrete is 94.66 yuan / m 2 ;
[0060] 2) When SBS modified asphalt is used to replace the base asphalt, the water damage resistance index of permeable steel slag asphalt concrete (porosity of 19%) is 83.2%, the durability index is 3500 times / mm, and the comprehensive cost of 4cm thick ordinary permeable steel slag asphalt concrete is 83.78 yuan / m 2 .
[0061] Embodiment 2:
[0062] A high-performance permeable asphalt steel slag concrete, which is different from Example 1 only in that it includes the following components and their weight contents:
[0063]
[0064] This embodiment combines the preparation and testing methods of permeable asphalt concrete specimens in the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011):
[0065] 1) The water damage resistance index of high-performance permeable steel slag asphalt concrete (porosity of 15%) is 96.3% (freeze-thaw splitting strength ratio of Marshall specimen), and the durability index is 5100 times / mm (dynamic stability of rutting plate specimen). The comprehensive cost of 4cm thick high-performance permeable steel slag asphalt concrete is 95.73 yuan / m 2 ;
[0066] 2) When SBS modified asphalt is used to replace the base asphalt, the water damage resistance index of permeable steel slag asphalt concrete (porosity of 17%) is 85.1%, the durability index is 4200 times / mm, and the comprehensive cost of 4cm thick ordinary permeable steel slag asphalt concrete is 84.15 yuan / m 2 .
[0067] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing permeable asphalt steel slag concrete, characterized in that: The following steps are involved: S1: Mix steel slag fine aggregate, matrix asphalt and limestone powder evenly to obtain filling and reinforcing aggregate; S2: Mix the filling reinforcement aggregate with basalt coarse aggregate, SBS modified asphalt and asphalt enhancer, mix them evenly, and obtain permeable asphalt steel slag concrete; The mass ratio of the basalt coarse aggregate, steel slag fine aggregate, limestone powder, matrix asphalt, SBS modified asphalt, and asphalt enhancer is (68-72):(17-20):(4.4-4.9):(1.3-1.5):(4.8-5.0):(0.5-0.6); The steel slag fine aggregate includes the following components and contents by weight: 8-10 parts of steel slag fine aggregate with average particle size of 4.75-2.36 mm; 6-7 parts of steel slag fine aggregate with an average particle size of 2.36-1.18 mm; 3 parts of steel slag fine aggregate with average particle size of 1.18~0.075 mm; The limestone powder has a specific surface area of 5000-8000cm 2 / g, particle size distribution D90 is 55-65μm, and apparent relative density is 2.85-3.05g / cm 3 ; The basalt coarse aggregate includes the following components and contents by weight: 0-3 parts of basalt coarse aggregate with an average particle size of 16.0-13.2 mm; 50-58 parts of basalt coarse aggregate with an average particle size of 13.2-9.5 mm; 11-18 parts of basalt coarse aggregate with an average particle size of 9.5-4.75 mm; The asphalt enhancer contains 0.18 wt% of tetrasodium ethylenediaminetetraacetate; In the SBS modified asphalt, the mass ratio of the linear modifier SBS to the base asphalt is 4.5:
100.
2. The method for preparing permeable asphalt steel slag concrete according to claim 1, characterized in that: In step S1, the mixing time is 30 to 60 s.
3. The method for preparing permeable asphalt steel slag concrete according to claim 1, characterized in that: In step S2, the mixing time is 60 to 120 s.
4. A permeable asphalt steel slag concrete, characterized in that: The method is prepared by the method according to any one of claims 1 to 3.
Citation Information
Patent Citations
High-strength steel slag concrete and preparation method thereof
CN112759304A